Analyzing the Influence of Knowledge Management and Innovation on the Competitive Advantage of Creative MSMEs in Medan Polonia City: A Quantitative Approach - Nasution, Edwin Sugesti (Quantitative Economics and Management Studies, 2025)
This study aims to analyze the influence of knowledge management and innovation on competitive advantage among micro, small, and medium enterprises (MSMEs) in the creative sector in Medan City. The research focuses on MSME actors located in Medan Polonia District, a prominent hub for creative economic activities with dynamic business growth. A quantitative approach was employed using a survey method and structured questionnaires distributed to 100 respondents. Data were analyzed using multiple linear regression with the aid of SPSS version 26. The results reveal that both knowledge management and innovation have a significant and positive influence on competitive advantage, both partially and simultaneously. Among the dimensions of knowledge management, knowledge sharing emerged as the most dominant indicator, while collaborative innovation was the leading factor within the innovation variable. These findings indicate that integrating systematic knowledge processes with a continuous innovation culture enhances MSMEs’ ability to compete, respond to customer needs, and offer uniqueness in their products and services. This study supports the resource-based view (RBV) and dynamic capabilities theory, which suggest that knowledge and innovation are strategic, inimitable resources that drive long-term competitive advantage. The practical implications emphasize the importance of training, digitalization, and collaborative innovation ecosystems to strengthen the competitive capacity of MSMEs in Indonesia’s creative industries. Future studies are recommended to examine the role of digital literacy, leadership, and technological readiness as supporting variables in the sustainable development of competitive advantage among MSMEs.